PEMAHAMAN KONSEPTUAL SISWA DALAM MENYELESAIKAN SOAL MATERI INVERS MATRIKS PADA KELAS XI SMAN 8 PONTIANAK - Herdiwibawa, Junior Putra; Jamiah, Yulis; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractOne of the goals of mathematics in secondary education is that students have the ability to understand mathematical concepts, explain the links between concepts and apply concepts or algorithms flexibly, accurately, efficiently and precisely in problem solving. This study aims to determine students' conceptual understanding in terms of the high-level previous ability group and the medium-level previous ability group in solving the inverse matrix material problem in class XI Sains Senior High School Number 8 Pontianak. The research method used descriptive with survey research. The data source of this study was class XI Sains 2 and the data were answer sheets for the conceptual understanding test and student interview results. The results of the study show that the conceptual understanding of the students of the high-level previous ability group of students has been able to mention the inverse matrix definition and write singular matrix and non-singular matrix. For students of the previous ability group of medium level students have not been able to distinguish matrix that have inverses and those that do not, have not been able to write singular and non singular matrix and have not been able to choose certain procedures or operations to determine an inverse matrix.Â Keywords: Conceptual Understanding, Previous Ability, Inverse Matrix